Education for Sustainable Development Based on Technological Pedagogical Content Knowledge in Biology Education: Assessing Teachers' Readiness - Anwar, Yenny; Widodo, Ari; Al fatih, Zaky; Kartika, Diah; Ariska, Meli; Yusliani, Novi (Universitas Negeri Semarang, 2025)
Teachers’ readiness to integrate Education for Sustainable Development (ESD) plays a pivotal role in preparing students to understand and practice sustainable living. This study examined the readiness of 232 in-service biology teachers in South Sumatra, comprising 142 novice teachers (with ≤10 years of experience) and 90 experienced teachers (with>10 years of experience). A descriptive-comparative quantitative design was employed, using two structured questionnaires to measure teachers’ perspectives on ESD and their Technological Pedagogical Content Knowledge (TPACK). Findings revealed that teachers generally showed a strong commitment to ESD but only a moderate conceptual understanding. Within TPACK, attitudes were rated the highest, whereas technological and inquiry-based competencies were rated the lowest. Novice teachers scored higher than experienced teachers, while participation in environmental education training or prior teaching experience in related topics improved readiness. This study highlights the importance of continuous professional development in enhancing teachers’ technological and inquiry-oriented capacities. Strengthening these dimensions is crucial for effectively embedding ESD into biology teaching and science education more broadly. By addressing these gaps, the integration of ESD can move beyond awareness toward transformative learning that equips students with the skills and dispositions needed for sustainable futures.